Multi-Itinerary Optimization as Cloud Service - Cristian, Alexandru; Marshall, Luke; Negrea, Mihai; Stoichescu, Flavius; Cao, Peiwei; Menache, Ishai (ACM SIGSPATIAL 2019, 2019)
In this paper, we describe Multi-Itinerary Optimization (MIO) - a novel Bing maps service that automates the process of building itineraries for multiple agents while optimizing their routes to save travel time or distance. MIO can be used by organizations with a fleet of vehicles and drivers, mobile salesforce, or a team of personnel in the field in order to maximize workforce efficiency. MIO accounts for service time windows, duration, and priority, as well as traffic conditions between locations, resulting in challenging algorithmic problems at multiple levels (e.g., calculating travel-time distance matrices at scale, scheduling services for multiple agents). To support an end-to-end cloud service with turnaround times of a few seconds, our algorithm design targets a sweet spot between accuracy and performance. Towards that end, we build a scalable solution based on the ALNS meta-heuristic. Our experiments show that accounting for traffic significantly improves solution quality: MIO not only avoids violating time-window constraints, but also completes up to 17% more services compared to traffic-agnostic mechanisms. Further, our solution generates itineraries with better accuracy than both a cutting-edge heuristic (LKH3) and an Integer-Programming based algorithm, with twice and orders-of-magnitude faster running times, respectively.
Best-paper candidate